Managemen Kesan Anak Perempuan Pertama dalam Peran Parentifikasi: Studi Dramaturgi di Keluarga - Raihanah Humaira; Al Kayla Tatstiana Legowo; Reni Nuraeni; Sri Damayanti (Jurnal Keluarga Sehat Sejahtera, 2026)
The phenomenon of parentification in firstborn daughters is often viewed as a natural form of responsibility. Yet such roles are typically associated with adults. This study focuses on how firstborn daughters engage in impression management while fulfilling their parentified roles within the family environment, through the lens of Erving Goffman’s dramaturgical perspective. This study also examines how this role is manifested in daily interactions and how individuals manage experiences that do not always surface within the family interaction space. Using a qualitative approach and focusing on a comprehensive understanding of the phenomenon, data were collected through in-depth interviews with informants divided into two cross-generational groups: Gen X and Gen Z. The results indicate that firstborn daughters project an image of independence and resilience on the front stage to maintain family stability, while their back stage often functions as a space of emotional isolation. This study concludes that firstborn daughters frequently present themselves as independent, strong, and responsible figures in front of the family. This role is not merely an act, but a reflection of the upbringing they received from a young age, which compelled them to not only be an older sibling but also a surrogate parent to maintain household harmony.